The arrival of naturalism in Spain through the finisecular press - López Martín, Ismael (2020)
With the selection of ten articles published in newspapers of different ideologies of the last years of the nineteenth century, the following pages outline the development of one of the most important controversies in the history of literature and culture almost from the secular debate between classical and modern: the incorporation of Spain to the naturalistic aesthetic, born in France. These disputes, which did not go unnoticed any intellectual, were characterized by confusion in terminology, the intransigence of ideals, the understanding of the new school as a link in the advancement of literature and the fierce critic of the Catholic religion.